منهج الشيخ عبد الحق الدهلوي في خصائص النبي (عرض وتعقيب على ضوء عقيدة أهل السنة والجماعة): Sheikh Abdul-Haq al-Dahlawi's Approach to the Characteristics of the Prophet (Presented and Commented Upon Considering the Doctrine of Ahl al-Sunnah Wa al-Jamāʿah) - Muhammad Mahmud Al Hasan (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
In this research, I shed light, to the best of my ability, on the following elements: (1) a brief biography of al-Dahlawi, (2) al-Dahlawi's approach to the characteristics of the Prophet ﷺ and the doctrinal violations he cited without providing evidence for them from the Qur'an and Sunnah, (3) a commentary on these characteristics in light of the doctrine of Ahl al-Sunnah wal-Jama'ah. This is achieved by following an inductive analytical approach, whereby the characteristics not proven by the Qur'an and Sunnah are collected from al-Dahlawi's works, followed by an analysis based on the Qur'an, Sunnah, and the sayings of the righteous predecessors to determine the extent to which the sheikh agrees with the doctrine of Ahl al-Sunnah. The research extracts the following results from it: 1) al-Dahlawi is a renowned scholar, especially in the Indian subcontinent, and author of numerous works on the doctrine of the Ash'aris and the Sufi order. 2) al-Dahlawi differed from Ahl al-Sunnah wal-Jama'ah regarding some of the characteristics of the Prophetﷺ , and this is considered an exaggeration in his praise of the Prophet ﷺ. 3) There is no authentic evidence that the first of creations was our Prophet Muhammad ﷺ or his spirit. 4) There is no authentic evidence to indicate this, and the claim that the Prophet ﷺ parents embraced Islam and were saved contradicts the Quran, the Sunnah, and the consensus. 5) The prophets are alive in their graves, and this life is a life in the intermediate realm, not a worldly life. 6) It has been proven that the control of the universe is the exclusive property of Allah Almighty, and no one shares it with Him, neither prophet nor angel. Ad-Dahlawi (may Allah forgive him) also disagreed on this and affirmed that other prophets and saints can control the universe.